Introducción al estudio de las poblaciones costeras durante la etapa arcaica en el norte de Chile - Muñoz Ovalle, Iván (1985)
Research carried out in recent years has released important findings regarding the first populations that inhabited the north coast of Chile. For this reason, we have been interested in preparing, by way of synthesis, an article that analyzes the forms of adaptation and development of these populations to coastal life. In it, some aspects of their culture are discussed, which are not only important for the studies of this Central South Andean cultural area (Lumbreras, 1981), but also of the total Andean and American areas in general.